Effect of factors on dielectric properties of pineapple leaf for microwave application - Azahani Natasha, Azman; Nurfarhana, Mustafa; Giamasrow, Rudraa Devi; Nurhafizah, Abu Talip Yusof; Norazwina, Zainol; Mohamad Shaiful, Abdul Karim (Elsevier Ltd, 2024)
Nowadays, dielectric materials are widely used in electronic applications, and their permittivity and loss tangent are important properties to consider. Dielectric materials made from waste can help reduce pollution and conserve resources. The aim of this work is to analyze the important factors in pineapple plantation waste preparation as dielectric materials using rapid two-level factor analysis in order to identify significant factors during preparation. It takes a short procedure to determine the optimum variable factor and leads to fast analysis. The dielectric material preparation process involves chemical treatment, sample fabrication, and sample characterization. Measurement of permittivity is performed by using a G-band rectangular waveguide. The highest dielectric permittivity is 3.31 where one of the suitable applications is used as an antenna substrate. The best factor in producing high dielectric permittivity is a 1:10 ratio of pineapple leaves to distilled water, 50 min of boiling time, using a heating effect, and 5 g weight of pineapple leaves powder. The most significant factor in producing high dielectric permittivity is the heating effect, which is contributed by the presence of carbon in the composite material.